The TanDEM-X mission: A satellite formation for high resolution SAR interferometry - Krieger, Gerhard; Fiedler, Hauke; Zink, Manfred; Hajnsek, Irena; Younis, Marwan; Huber, Sigurd; Bachmann, Markus; Hueso-Gonzalez, Jaime; Werner, Marian; Moreira, Alberto (European Microwave Week (EuMW), 2007)
TanDEM-X (TerraSAR-X add-on for Digital Elevation Measurements) is an innovative spaceborne radar interferometer mission that was approved for full implementation by the German Space Agency in spring 2006. This paper gives an overview of the TanDEM-X mission concept, summarizes the basic products, illustrates the achievable performance, and provides some examples for new imaging modes and applications. © 2007 EuMA.
DLR Import::2019-04-03